PENYELENGGARAAN PROGRAM PAKET B DI PKBM AMANAH UMMAT KELURAHAN BATUA KECAMATAN MANGGALA KOTA MAKASSAR - Wahyuni, Widha; Latang, Latang; Gaffar, Fatmawati (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
ABSTRACTThis study aims to determine the implementation of the package B program at PKBM Amanah Ummat, Batua Village, Manggala District, Makassar City. This research uses a qualitative approach and a case study type of research. The subjects of this study were 1 manager/chairman of PKBM Amanah Ummat and 4 package B tutors. The data for this study were collected by observation, interview and documentation techniques. Data is processed by data reduction, data presentation, as well as conclusions and verification. The results showed that this study examined the implementation of the package B program at PKBM Amanah Ummat, Batua Village, Manggala District, Makassar City through 3 stages, namely: planning which included preparing lesson plans and syllabus; Implementation which includes grouping learning residents, providing learning media and resources, making learning schedules and providing facilities and infrastructure, providing motivation for learning residents, learning skills and methods; Assessment of learning outcomes, at this stage aims to measure the extent to which the learning community is able to participate in the package B learning process at PKBM Amanah Ummat.Keywords: Implementation, program, package B, PKBM